2017
DOI: 10.4081/rt.2017.6420
|View full text |Cite
|
Sign up to set email alerts
|

Granular Cell Tumor of Cecum: A Common Tumor in a Rare Site with Diagnostic Challenge

Abstract: Granular cell tumor (GCT) also known as Abrikossoff’s tumor is a benign neoplasm that is usually seen in the fourth to sixth decades of life with slight female preponderance. It is most frequently seen in the oral cavity, skin, and subcutaneous tissue. Gastrointestinal tract involvement is uncommon, in which esophagus is the most commonly affected site. There are case reports of GCT in stomach, appendix, colon and rectum. In this article, we report a case of GCT involving cecum. The cell of origin in GCT is co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 20 publications
0
16
0
Order By: Relevance
“…GCTs are mainly found in patients in their fourth to sixth decades of life and have a female predominance with a 2:1 ratio [2]. These are thought to be derived from the neural tissue (Schwann cells); however, other cell lineages have been proposed as histopathogenesis [3-4].…”
Section: Discussionmentioning
confidence: 99%
“…GCTs are mainly found in patients in their fourth to sixth decades of life and have a female predominance with a 2:1 ratio [2]. These are thought to be derived from the neural tissue (Schwann cells); however, other cell lineages have been proposed as histopathogenesis [3-4].…”
Section: Discussionmentioning
confidence: 99%
“…50% of GHTs in the head and neck are located in the oral cavity. It is predominantly seen in women in the 4th and 5th decades (1,2,5,8,9). It was first reported by Weber in 1854 and then by Abrikossoff in 1926.…”
Section: Discussionmentioning
confidence: 99%
“…It is thought to develop from skeletal muscle, histiocytes, fibroblasts, nerve sheath cells, neuroendocrine cells and differentiated mesenchymal cells (2). Recent immunohistochemical and electronmicroscopic studies have shown that the origin of these tumors is "schwann "cells (1,2,9). While GCT is immunohistochemically stained with S100, p75, NSE and CD68, inhibinα, and vimentin, it is not stained with smooth muscle actin (SMA), epithelial membrane antigen, HHF-35, synaptophysin, chromogranin, progesterone, androgen, estrogen, carcinoembryonic antigen (CEA), and PanCK (2,3,9).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations